-2(7u-4)+5u=3(u+2)

Simple and best practice solution for -2(7u-4)+5u=3(u+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7u-4)+5u=3(u+2) equation:


Simplifying
-2(7u + -4) + 5u = 3(u + 2)

Reorder the terms:
-2(-4 + 7u) + 5u = 3(u + 2)
(-4 * -2 + 7u * -2) + 5u = 3(u + 2)
(8 + -14u) + 5u = 3(u + 2)

Combine like terms: -14u + 5u = -9u
8 + -9u = 3(u + 2)

Reorder the terms:
8 + -9u = 3(2 + u)
8 + -9u = (2 * 3 + u * 3)
8 + -9u = (6 + 3u)

Solving
8 + -9u = 6 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
8 + -9u + -3u = 6 + 3u + -3u

Combine like terms: -9u + -3u = -12u
8 + -12u = 6 + 3u + -3u

Combine like terms: 3u + -3u = 0
8 + -12u = 6 + 0
8 + -12u = 6

Add '-8' to each side of the equation.
8 + -8 + -12u = 6 + -8

Combine like terms: 8 + -8 = 0
0 + -12u = 6 + -8
-12u = 6 + -8

Combine like terms: 6 + -8 = -2
-12u = -2

Divide each side by '-12'.
u = 0.1666666667

Simplifying
u = 0.1666666667

See similar equations:

| a^2-x-20=0 | | -2(6w-5)+6w=8+4(3w-1) | | 20.48=u/8 | | w+(w+3)+w+(w+3)=42 | | 40x=39(x+45) | | (5X-2)+2x=8 | | X/-15=4 | | 5x+4=.25 | | Ix+cI=C | | 0.7(8x+16)=1.6-(x+2) | | (2-X)+5=7 | | 9x/(7x-14) | | 2x-4x+3x-4+5x= | | a^2-22a+185=0 | | 3/2(20)-4 | | Xsquared-6x=6 | | 2w+3=4w+-5 | | 3+2q-(4q+9)-(5q+6)= | | 6(x+3)-3(x+2)=27 | | 57-(5x+4)=5(x+4)+x | | 24=16tsquared | | 26x-8-16x+2=26x-4-16x+17 | | 6(2+4y)=2y+4y+8y | | 3.5(1)=3.5 | | x/0.9=7.2 | | (72y^3)/(64y^7) | | ((x)/(0.01-x)(0.02-x))=0.45 | | 10p+56=176-p | | (72y^3/64y^7) | | b/6=-28 | | (3x/5)-7=(2x/6)+1 | | 72y^3/64y^7 |

Equations solver categories